Epidemiology and outcomes of ischemic stroke treatment in two public hospitals of Campos dos Goytacazes, RJ. - Renon, Talles Falqueto (2020)
Background: The main origin of functional dependence in Brazil and the world is the ischemic stroke. The early thrombolytic treatment reduces this morbidity. However, the extended in-hospital delay is the main risk factor for the suboptimal number of ischemic stroke patients who receive this treatment. Objective: To describe the management of patients admitted with ischemic stroke in two Brazilian public hospitals. Methods: This cross-sectional study was carried out in two emergency units in 2016 in Campos dos Goytacazes: Hospital Ferreira Machado (HFM) and Hospital Geral de Guarus (HGG). We analyzed the prevalence of sex, age, risk factors, time of first symptoms, prescription of thrombolytic therapy and contraindications to its use. Results: None of the 130 patients with ischemic stroke received a prescription of rt-PA, even though HFM had rt-PA available throughout the period of the study. HGG does not keep this data documented. Of all, 41 patients died (31,54%). Advancing age (p < 0.0005) and atrial fibrillation 3.458 (CI = 95%, 1.239 to 10.16, p = 0.0238) were risks factors for the mortality in this population. Conclusions: The lack of information in medical records reveals that low staff training may be the main reason why thrombolytic therapy was not prescribed. The elevated mortality rate shows that medical care for patients admitted with ischemic stroke in our region is far from ideal.